A General Approach to Panel Data Set-Theoretic Research - Castro, Roberto Garcia; Ariño, Miguel A. (Journal of Advances in Management Sciences & Information Systems, 2016)
Academic research based on general linear statistical models has been rapidly moving toward a greater and richer use of longitudinal and panel data econometric methods. By contrast, set-theoretic empirical research, despite its growing diffusion, has been mainly focused on cross-sectional analysis to date. This article covers this void in panel data set-theoretic research. We provide some diagnostic tools to assess a set-theoretic consistency and coverage both cross-sectionally and across time. The suggested approach is based on the distinction between pooled, between and within consistency and coverage, which can be computed using panel data. We use KLD’s panel (1991–2005) to illustrate how the proposed approach can be applied in the context of set-theoretic longitudinal research.